Penyuluhan Kesehatan dan Pelatihan Pembuatan Pasta Gigi Herbal pada Orang Tua Siswa di SDN 09 Pontianak - Fathiah Fathiah; Indah Purwaningsih; Sunarsieh Sunarsieh; Budi Suryana; Meri Ropiqa (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Riskesdas data in 2018 showed that the number of tooth decays in West Kalimantan province was 49.55% and that in Pontianak City was 39.52%. The results of a preliminary survey conducted on 5th-grade students of SDN 09 Pontianak found an average of three deciduous teeth and four adult teeth affected by dental caries. One way to prevent dental caries is to brush the teeth using toothpaste that contain active antibacterial ingredients. One herb widely used as an active ingredient in toothpaste is siwak. This community service activity aims to increase knowledge and skills in making herbal toothpaste to reduce the dental plaque index. This activity uses health counseling methods through lectures, leaflet distribution, and training on making herbal toothpaste from siwak. This activity was conducted in collaboration with SDN 09 Pontianak and was held on Friday, June 24, 2022, with 53 participants. From this activity, the participants received education on the benefits of herbal toothpaste for dental and oral health. In addition, this training activity can increase creativity and skills in creating herbal toothpaste and foster an entrepreneurial spirit. After this activity, it will continue with training activities with the theme of entrepreneurship as part of efforts to downstream and commercialize herbal toothpaste products.